Utilização da tecnologia RFID na automação do canteiro de obras visando à melhoria da segurança do trabalho - Oliveira, Victor Hugo Mazon de (2018)
The economic expression of the construction industry in relation to the national economic structure establishes it as one of the main sectors of the national production chain. On the other hand, the sector faces problems such as the high rate of occupational accidents and the high waste of resources. This context provides the opportunity to introduce new technologies for the development of management tools in order to make the work environment more efficient, integrated, and secure. In this sense, the proposed research aims to develop a system for monitoring and controlling fall risk areas and managing safety equipment using Radio Frequency Identification (RFID) technology. It is expected with this study to demonstrate the viability of the proposed system by identifying its contribution to reducing the risk of accidents on the construction site using information technology as remote monitoring tools. The research method adopted is based on Design Science Research (DSR) to support the problem solving and the development of an artifact based on RFID technology. The proposed control and monitoring system assemble two distinct functions: (1): monitoring and control of risks of falls from heights and (2) monitoring and control of collective safety equipment. To coordinate and unify the two functions, it was developed the software entitled: “Monitoramento da Segurança do Canteiro de Obras via RFID” and an app for the Andoid platform entitled: “Monitora RFID”. The software and the app manage the tool functions by storing and organizing the database. The results are generated using spreadsheets, graphics, and plan images. The testing routine combines laboratory testing for methodology development and validation and testing at an operating site for system verification in a real building environment. The results introduce a system organized by a protocol of procedures for the reproduction and application of the tool. The tests validated the proposal and the results were consistent demonstrating the partial operational viability of the system.